(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Some 1-Nicotinoyl-4-aryl-3-methyl 3a, 4-dihydropyrazole [3, 4c] pyrazoles were synthesised and their inclusion complexes were prepared with β-cyclodextrin. The compounds and their inclusion complexes were characterised by the study of their physical and spectral properties. The determination of stability constant of inclusion complexes and other thermodynamic parameters such as change in free energy, change in enthalpy and change in entropy, suggested the inclusion complex formation to be thermodynamically allowed. Further, the compounds and their inclusion complexes were screened for antibacterial activities against Escherichia coli (MTCC 40), Bacillus subtilis (MTCC 441), Staphylococcus aureus (MTCC 87) and Proteus vulgaris (MTCC 426). It was found that that the formation of inclusion complex causes an increase in antibacterial activity.